2018
DOI: 10.1089/dna.2017.3690
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Treatment of Prostaglandin E1 and Angiotensin-Converting Enzyme Inhibitor in Diabetic Kidney Disease Rats: Possible Role of Antiapoptosis in Renal Tubular Epithelial Cells

Abstract: To investigate the therapeutic mechanisms underlying prostaglandin E1 (PGE1) and angiotensin-converting enzyme inhibitor (ACEI) on reducing urinary protein in diabetic kidney disease (DKD). DKD rats were established and randomly divided into four groups: PGE1 (10 μg/kg/day) (P group), ACEI (10 mg/kg/day) (A group), combination of PGE1 with ACEI treatment (P + A group), and saline treatment group (DKD group). Untreated rats were used as normal control (N group). Urinary albumin, endothelin-1 (ET-1), angiotensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…There was an elevated level of microalbuminuria in the DKD group compared with that in the sham and Unx groups on day 38 ( P < 0.05, Fig. 1d ), in accordance with previous findings in the DKD model [ 25 ]. Additionally, the level of microalbuminuria in the PGE1 group decreased compared with that in the DKD group after 10 d of PGE1 treatment, and the difference was statistically significant ( P < 0.05, Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…There was an elevated level of microalbuminuria in the DKD group compared with that in the sham and Unx groups on day 38 ( P < 0.05, Fig. 1d ), in accordance with previous findings in the DKD model [ 25 ]. Additionally, the level of microalbuminuria in the PGE1 group decreased compared with that in the DKD group after 10 d of PGE1 treatment, and the difference was statistically significant ( P < 0.05, Fig.…”
Section: Resultssupporting
confidence: 92%
“…In addition, PGE1 inhibits apoptosis via the downregulation of Bax expression and the upregulation of Bcl-2 expression in neonatal rat cardiomyocytes under hypoxic conditions [ 24 ]. Previously, we found that PGE1 alleviates urinary protein levels by inhibiting the apoptosis of renal tubular epithelial cells in DKD rats [ 25 ]. Notably, illuminating how PGE1 affects proximal renal tubular apoptosis might be helpful for identifying the pharmacological mechanism of PGE1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations